Impact of an Asynchronous E-learning Intervention on Cancer Knowledge and Clinical Practice for Pre-registration Nursing and Allied Health Professions Students and Cancer Support Workers - Julie Armoogum; June Davis; John Gale; Vanessa Taylor (Journal of Cancer Education, 2026)
Abstract Pre-registration nursing and allied health professions students and cancer support workers can feel unprepared to care for people affected by cancer and at the end of life. To address this need, nine e-learning modules, collectively called ‘Foundations of Cancer Care’, have been developed aligned to the NHS England ACCEND Framework. The resultant programme is freely available to anyone with a UK email address via the NHS Learning Hub. To evaluate accessibility, structure, relevance, design and style of this nationwide digital education programme, and to understand the impact of the porgramme on cancer specific knowledge and clinical practice, an e-survey was developed based on the Kirkpatrick model of evaluation. On completing the programme, participants were invited to participate in the survey. Anonymised data were collated via the NHS Learning Hub and analysed using descriptive statistics. There was a mean of 343 distinct users per module and 123 participated in the evaluation. Most participants were student nurses (n=42, 33.9%) or support workers (n=35, 28.6%). In total, 88.6% (n=109) of participants rated the overall programme as good/very good. Over 90% agreed/strongly agreed that they had improved their knowledge and understanding of the impact of cancer on individuals, families and society (n=111). When asked how likely they would be to recommend the programme to their peers on a scale of 0-10 where 0 = not at all and 10 = extremely likely, 86.7% (n=105) rated a 5 or higher and 32.2% (n=39) rated 10 (extremely likely). Almost all thought the programme would help them with their role (n=111, 91.0%) and 89.4% (n=110) reported they would be able to use what they have learned in their clinical practice. This demonstrates that a digital education programme can increase knowledge and understanding of cancer care and is acceptable to users and their learning can be used in clinical practice. It is important to embed this digital intervention in pre-registration healthcare programmes and training and development opportunities for support workers providing care to people affected by cancer.